2017
DOI: 10.1111/sms.12899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exergames on musculoskeletal pain: A systematic review and meta‐analysis

Abstract: The main objective was to systematically review the scientific literature about the effects of exergame-based interventions on musculoskeletal pain, as well as to provide directions for the clinical practice. A systematic search was conducted in four electronic databases following PRISMA guidelines. The inclusion criteria were as follows: (a) the subjects were suffering musculoskeletal pain, (b) the study was randomized controlled trial (RCT), (c) intervention was based on exergames, (d) the article was writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 36 publications
3
16
1
Order By: Relevance
“…These findings are in keeping with other studies which have implemented exergaming, conducted in post-stroke patients [ 56 ], those having undergone a knee replacement [ 70 ] and also with UE dysfunction [ 71 ]. A systematic review also revealed that four of seven studies found significant improvements in musculoskeletal pain following exergaming interventions [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in keeping with other studies which have implemented exergaming, conducted in post-stroke patients [ 56 ], those having undergone a knee replacement [ 70 ] and also with UE dysfunction [ 71 ]. A systematic review also revealed that four of seven studies found significant improvements in musculoskeletal pain following exergaming interventions [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence of therapeutic benefits from exergaming [43,95,96], published studies on the effects of exergaming on pain are varied and inconsistent [97]. Many suggest an association between exergaming and pain [98] but few report significant changes in pain after exergaming [98,99].…”
Section: Painmentioning
confidence: 99%
“…42 Serious games also have the potential to improve the motivation to exercise, 24,25 but this has mostly been shown in studies lasting only 4-6 weeks. 24,43 Because patients with CLBP typically need to exercise for a longer period, 11 and motivation might decrease over time, 26 we investigated this during an 18-week intervention. The results from our study showed that patients remained motivated and satisfied throughout the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Research in patients with musculoskeletal pain shows that it is feasible to integrate SGs into rehabilitation programs. 43 However, most studies only used supervised exercise programs in hospitals or rehabilitation centers, where the technological system is set up by a therapist. 20,43 For patients with CLBP, home exercises are an important part of the rehabilitation and, as such, technological support should ideally be provided at home.…”
Section: Discussionmentioning
confidence: 99%